Raman spectroscopy of carbon nanostructures: from transistor to agriculture - Vasconcelos , Ado Jório de (Physicae Proceedings, 2020)
The carbon nanostructure was always in our life. It is rather surprising to think that graphene (a graphite sheet) has been considered today as a material that will replace silicon technology in our future. This lecture is an exercise done for the understanding of how scientific advances always make us go beyond. The advances are analyzed from the point of view of Raman spectroscopy. How come that a simple physical process, such as inelastic scattering of light, gives us the tools for the development of nanotechnology? - which means no more than the mastery by man of processes often conducted in nature.